Home health care in Japan: A call of the raised voice - Cahyani, Nindhi Zuhria; Shintaro, Watanabe (Universitas Muhammadiyah Magelang, 2021)
Providing home care to older people remains challenging in Asia countries such as Japan. The different cultures lead nurses to assist in different ways of care. As a nurse from abroad, delivering nursing care in other country need specific skills and knowledge to optimize the care. In addition, innovation is also needed for its efficiency during elderly care. Hopefully, this experience will motivate nurses to work in-home care service with heart instead of relocating to a retirement or long-term care facility as they get older.